Pembuatan Aplikasi Peminjaman Berkas Rekam Medik Berbasis Web di RSUP Klaten - Moh Maulana; Andri Permana Wicaksono; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Medical records according to Permenkes No. 269 of 2008 is a file containing notes and documents about patient identity. The problem that often arises in Klaten General Hospital is the length of the file search process due to the absence of applications that control the entry and exit of files, when officers borrow and return only to write in the control book. Supporting all the problems and objectives needed by the data, so the data collection methods used are observation and interviews. Analysis of the data obtained from the interview and observation process is to draw conclusions and identify the most urgent problems. The goal to solve this problem is to make an application that controls the borrowing and return of the RM file so that the officer knows quickly where the file will be sought. The application is made using the waterfall method in the workflow process and uses several programming languages such as PHP, HTML and CSS. The results of the application have been tested by several users using blackbok testing, but still do not know how effective and efficient when the application is tested in actual service.